Strategi Pengendalian Inflasi dalam Perspektif Ekonomi Islam - Rahma Detik Kuriningsih; Iiz Izmuddin; Hardiansyah Padli (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2023)
Inflation is a problem that is always faced in the economy, and inflation is also the main agenda of politicians and government policy makers. This research aims to find out how to control inflation from an Islamic Economics perspective. This research is a literature study. Sources of information and data used in articles come from scientific journals and books that are appropriate to the topic being studied. The research results reveal that inflation can be controlled through the implementation of a Sharia-based monetary system, currency management from an Islamic perspective, fair distribution of income and investment in the productive sector as well as supervision and regulation through economic regulations. This research provides a new contribution by combining conventional economic analysis with the principles of Islamic Economics in understanding and overcoming inflation. The results of this research show that the inflation control strategy from an Islamic Economics perspective offers a comprehensive and sustainable solution, taking into account moral, social and economic dimensions. Implementing these strategies requires strong commitment from all parties. This research paves the way for further, more in-depth research on the implementation of inflation control strategies from an Islamic Economics perspective in various contexts and scales.